RF06 Children presenting with chronic pain to the english national health service: a whole-population administrative data cohort study. (3rd September 2019) - Jay, MA; Howard, RF; Gilbert, R
Abstract : Background: Management of paediatric chronic pain (CP: pain >3 months' duration) is challenging and associated with significant comorbidities. Although large numbers of children may be affected, this population in England has not been well-described. In addition, despite partial provision of specialist NHS CP services, referral pathways are not well-established; children may therefore be receiving suboptimal interventions and access to CP services may be inequitable. We examined the characteristics and service utilisation of all children attending specialised CP services in England to inform commissioners and service providers. Methods: We used the Hospital Episode Statistics—data covering all NHS-funded inpatient admissions, outpatient appointments and A&E attendances in English hospitals. Children aged 10–17 first seen by a CP service between 2007/8 and 2016/17 were identified using service specialty codes that identify CP services. The presence of comorbid chronic conditions (e.g., cancer, neurological disorders or mental health conditions) in the five years prior to the first attended CP appointment (CP1) were identified from inpatient data using a validated ICD-10 code list. Service utilisation was described by histograms and rates of outpatient attendances, planned and emergency admissions and A&E attendances. Analyses were conducted in R. Results: There were 3, 185 (28%) boys and 8, 330 (72%) girls. In boys, 24% lived in the most deprived fifth of neighbourhoods in the country and 17% in the least deprived fifth; in girls, no such gradient was observed with 20% in all fifths. Comorbidity prevalence was high: 55% of boys and girls had some other chronic condition in the five years prior to CP1. There was a rise in outpatient attendances, emergency admissions and A&E attendances in the two years prior to CP1, with rises in emergency admissions and A&E attendances most striking. For example, the rate of emergency admissions 21–24 months prior to CP1 was 11.7 (95% CI 10.8, 12.6) per 100 person-years; in the three months prior to CP1, it was 38.3 (95% CI 36.7, 39.9). All abated after CP1. There was a spike of planned admissions after CP1 with a flat trend beforehand. Conclusion: Children presenting to CP services exhibit high degrees of physical and mental comorbidity. We found patterns of service utilisation indicative of unmet need prior to CP1 that warrants further investigation. Though our results may not generalise to all children with CP, this study suggests that earlier identification and referral could reduce unnecessary A&E visits and emergency admissions.